KELULUSHIDUPAN DAN PERTUMBUHAN LARVA IKAN BAUNG (Hemibagrus nemurus) DIBERI CACING SUTRA (Tubifex tubifex) YANG DIPERKAYA DENGAN PROBIOTIK DAN HABBATUSSAUDA (Nigella sativa) - Sinta Juliana; Rosyadi Rosyadi; Agusnimar Agusnimar (UIR Press, 2016)
Studies on the survival and growth of fish larvae baung by a silk worm enriched with probiotics and Habbatussauda has been done in Fish Seed Faperta UIR Riau Pekanbaru, from the month of February to March 2016. The purpose of the study to determine the survival and growth of fish larvae baung. The results showed survival rate of fish larvae best baung in treatment P2 (Probiotic + Habbatussauda Giving a dose of 0.2 mg / g diet) amounted to 91.33%. Baung fish larvae survival level highest in P2 at 91.33% and the lowest at 80.67% Po. The growth of absolute weight and length of the absolute highest was found in treatment P2 (Probiotic + Habbatussauda Giving a dose of 0.2 mg / g diet) each - each ie 0.4369 g and 3.67 cm.